2020
DOI: 10.1096/fj.202001951r
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of functional long noncoding RNAs in cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 171 publications
(363 reference statements)
0
7
0
Order By: Relevance
“…In recent years, abnormal expression of lncRNAs has been found to play a very important role in tumorigenesis and tumor progression. The study of new lncRNAs can also reveal a new mechanism of tumor development ( Sun et al, 2020 ; Olivero & Dimitrova, 2020 ; Zhang et al, 2021b ). Therefore, the exploration of new lncRNAs and the study of their biological functions will provide important impetus for tumor research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, abnormal expression of lncRNAs has been found to play a very important role in tumorigenesis and tumor progression. The study of new lncRNAs can also reveal a new mechanism of tumor development ( Sun et al, 2020 ; Olivero & Dimitrova, 2020 ; Zhang et al, 2021b ). Therefore, the exploration of new lncRNAs and the study of their biological functions will provide important impetus for tumor research.…”
Section: Discussionmentioning
confidence: 99%
“…While protein-coding determinants of metastatic cancer have been extensively studied, lncRNAs that contribute to metastatic progression are less well characterized and frequently lack experimental validation in relevant cancer models (Olivero and Dimitrova, 2020). In this study, we present conclusive evidence that the lncRNA Malat1 is a bona fide proto-oncogene and that Malat1 overexpression is sufficient to overcome the barrier to metastatic progression in the KP mouse model of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro CRISPRa experiments were performed with a previously described lentiviral vector (lenti-SAM-Hygro (Olivero et al, 2020)). In vitro CRISPRi experiments were performed with a lentiviral vector (lenti-KRAB-Hygro) constructed to co-express a U6-driven 15-mer ʻdead RNAʼ (dRNA) extended by two MS2 loops (dRNA-MS2), the transcriptional repressor KRAB (Kruppelassociated Box) fused to the MS2-binding protein (MBP), and a hygromycin-resistance gene.…”
Section: Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of recurrent cancer‐associated genetic aberrations in several lncRNA‐producing loci has raised the possibility that lncRNAs may be drivers, and not simply passengers, of cancer development (Beroukhim et al, 2010; Prensner & Chinnaiyan, 2011; Rheinbay et al, 2020). Efforts to model the recurrent genetic alterations of lncRNAs in cellular and organismal models of cancer have provided evidence that some lncRNAs are functional mediators of cancer‐relevant processes (Olivero & Dimitrova, 2020). These studies have revealed that genetic aberrations in lncRNA loci can contribute to the acquisition of cancer hallmarks, such as hyperproliferation, enhanced survival, altered metabolism, and increased metastatic dissemination (Huarte, 2015).…”
Section: Introductionmentioning
confidence: 99%